Attributes of panorama Melaka bus towards customer satisfaction / Muhammad Mubarak Ismail, Nur Sarafaten Mohd Noor and Amanina Athira Razlan - Ismail, Muhammad Mubarak; Mohd Noor, Nur Sarafaten; Amanina Athira Razlan, Razlan (Faculty of Hotel and Tourism Management, 2013)
Melaka’s bus system is set for improvements where in early 2012 the state government of Melaka assumed management of the city’s stage buses through its subsidiaries. By monitoring customer satisfaction is critical to help ensure a satisfying overall experience, customer value and repeat customers. Here, we examine customer satisfaction from data collection on Panorama Melaka Bus. The study focuses on identifying significant factor that influencing customer evaluation and satisfaction with the overall experiences by using that service. The key findings reveal that customer evaluate the services primarily on overall experience based on the tangible facilities that Panorama Melaka Bus provide. Core conditions of the buses must meet are responsiveness and the assurance of the services. Other features vary in importance.